Proceeding report of the Second Symposium on Hidradenitis Suppurativa Advances (SHSA) 2017. Issue 1 (15th January 2019) - Shavit, Eran; Alavi, Afsaneh; Bechara, Falk G.; Bennett, Richard G.; Bourcier, Marc; Cibotti, Ricardo; Daveluy, Steven; Frew, John W.; Garg, Amit; Hamzavi, Iltefat; Hoffman, Lauren K.; Hsaio, Jenny; et al.
Abstract: The 2nd Annual Symposium on Hidradenitis Suppurativa Advances (SHSA) took place on 03‐05 November 2017 in Detroit, Michigan, USA. This symposium was a joint meeting of the Hidradenitis Suppurativa Foundation (HSF Inc.) founded in the USA, and the Canadian Hidradenitis Suppurativa Foundation (CHSF). This was the second annual meeting of the SHSA with experts from different disciplines arriving from North America, Europe and Australia, in a joint aim to discuss most recent innovations, practical challenges and potential solutions to issues related in the management and care of Hidradenitis Suppurativa patients. The last session involved clinicians, patients and their families in an effort to educate them more about the disease.